2021
DOI: 10.1093/trstmh/traa182
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with Chikungunya infection in a cohort of women aged 15–39 y in Fortaleza, Brazil

Abstract: Background Outbreaks of Chikungunya virus (CHIKV) occurred in Brazil during 2015–2017. Fortaleza was the city that reported the most cases. Methods The first round of a cohort study was conducted among women aged 15–39 y in Fortaleza, Brazil, in 2018 (Zika in Fortaleza). We collected sera to detect CHIKV IgG and IgM antibodies. Factors for CHIKV infection were identified using a Poisson regression model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Studies in Brazil carried out in the northeast have identified frequencies between 20% to 57% [ 21 , 22 ]. A cohort study conducted in the city of Fortaleza (Ceará-Brazil) identified that 37.2% of women of childbearing age tested positive for CHIKV IgG antibodies [23] . Herein, we observed a much lower frequency of CHIKV IgG antibodies (7.6%), suggesting relatively low CHIKV circulation in the city of Salvador, which corroborates findings from a local populational study that reported a seroprevalence of 11.8% for CHIKV [24] .…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Brazil carried out in the northeast have identified frequencies between 20% to 57% [ 21 , 22 ]. A cohort study conducted in the city of Fortaleza (Ceará-Brazil) identified that 37.2% of women of childbearing age tested positive for CHIKV IgG antibodies [23] . Herein, we observed a much lower frequency of CHIKV IgG antibodies (7.6%), suggesting relatively low CHIKV circulation in the city of Salvador, which corroborates findings from a local populational study that reported a seroprevalence of 11.8% for CHIKV [24] .…”
Section: Discussionmentioning
confidence: 99%